2011
DOI: 10.3109/01443615.2010.545899
|View full text |Cite
|
Sign up to set email alerts
|

Significance of subchorionic haemorrhage and pregnancy outcome in threatened miscarriage to predict miscarriage, pre-term labour and intrauterine growth restriction

Abstract: Subchorionic haemorrhage in the 1st trimester of pregnancy can be seen in some patients and the significance of it is controversial. In this study, subchorionic haemorrhage was found to be significantly associated with increased risk of miscarriage and IUGR. On the other hand, we did not see a significant relation between pre-term labour and subchorionic haemorrhage. We hope these findings will help clinicians in their practice about pregnancy follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 8 publications
7
34
1
2
Order By: Relevance
“…The earliest and easiest definition of absolute size was the multiplied product of longitudinal, transverse, and antero-posterior diameters [3], [14]. Since the outline of most hematomas was not regular rectangle, mean of its three diameters [15], [16], half of the product [9], [17][20], or the product multiplied by a constant [8], [21], [22], were used by later researchers. Some authors recorded the size directly by the largest diameter or area observed [23], [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest and easiest definition of absolute size was the multiplied product of longitudinal, transverse, and antero-posterior diameters [3], [14]. Since the outline of most hematomas was not regular rectangle, mean of its three diameters [15], [16], half of the product [9], [17][20], or the product multiplied by a constant [8], [21], [22], were used by later researchers. Some authors recorded the size directly by the largest diameter or area observed [23], [24].…”
Section: Resultsmentioning
confidence: 99%
“…A hematoma of two-thirds or greater of the gestational sac circumstance was a good predictor of abortion when the analysis was adjusted for maternal age and gestational age at diagnosis (OR, 2.9; 95%CI, 1.2–6.8) [26]. Özkaya et al [20] used 32 ml as the grading standard and found that the volume of SCH was significantly larger in the miscarriage group than that of the normal delivery group (p = 0.003). Recently, a small prospective study also reported that the volume of a SCH showed a positive correlation with the incidence of abortion, especially when a hematoma larger than 4cm 2 [30].…”
Section: Resultsmentioning
confidence: 99%
“…1 Still others have estimated the relative volume of the SCH compared to the gestational sac 2,3,7-10,15 or calculated the SCH volume from measurements. [2][3][4]6,11,14,[16][17][18][19][20] Some have assessed the SCH location in the uterus, 4,5,10,14,15 and others have correlated symptoms and the presence of an SCH with pregnancy outcome. 1,[7][8][9][10]14 Because the published literature includes a broad variety of methods for characterizing an SCH, the reporting of an SCH identified on a first-trimester US examination is variable from practitioner to practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated calculating the volume of an SCH by measuring 3 orthogonal dimensions and applying the mathematical formula for the volume of an ellipsoid (approximately half of the product of the 3 dimensions). 2,4,6,14,[17][18][19][20] However, this approach is mathematically invalid and can yield very spurious results, since most SCHs have highly irregular shapes such that the formula for the volume of an ellipsoid is inapplicable. Thus, we recommend against trying to calculate SCH volume based on US measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because some obstetric patients, especially those presenting with vaginal bleeding, are examined in the emergency clinic. Özkaya et al found subchorionic haemorrhage to be significantly associated with increased risk of miscarriage and intrauterine growth restriction (IUGR) [30]. Therefore, we consider that diagnosing subchorionic haemorrhage in first trimester ultrasonography is important for pregnancy followup.…”
Section: Discussionmentioning
confidence: 99%